2000
DOI: 10.1046/j.1365-4362.2000.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in the pruritic papular eruption of HIV

Abstract: The lower levels of IL-2 and gamma-IFN and the negative correlation between gamma-IFN and peripheral CD4+ lymphocytes may indicate an early phase of immunosuppression in PPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…[2][3][4][5][6] The laboratory findings also included high levels of blood IgE and eosinophilia. 13,22 The present study did not demonstrate any epidemiological or clinical difference between the HIV-PPE and HIV-EF groups except for the bodily distribution of cutaneous lesions, although the sites of the lesions were the clinical criteria for diagnosis. Both diseases affected young male patients who were determined to be HIV positive approximately 3 years previously and presented a 3-to 5-month period of disease onset (see Table I).…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…[2][3][4][5][6] The laboratory findings also included high levels of blood IgE and eosinophilia. 13,22 The present study did not demonstrate any epidemiological or clinical difference between the HIV-PPE and HIV-EF groups except for the bodily distribution of cutaneous lesions, although the sites of the lesions were the clinical criteria for diagnosis. Both diseases affected young male patients who were determined to be HIV positive approximately 3 years previously and presented a 3-to 5-month period of disease onset (see Table I).…”
Section: Discussioncontrasting
confidence: 66%
“…13,22,23 In this study, blood eosinophil levels were low in both groups even when compared with the normal parameters. These data demonstrate that serum eosinophil determination does not contribute to the differential diagnoses.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Though in previous studies it was stated that lower levels of IL2 and gamma IFN and negative correlation between gamma IFN and peripheral CD4 lymphocytes may indicate an early phase of immunosuppression in PPE (23) but now it is considered as advanced sign of HIV Infection where majority of patients with PPE had CD4 count less than 200. (24) Several observational studies have reported that there is a link between low CD4 count and advanced HIV disease and as per WHO clinical staging it is included in stage III and IV and thus proposing PPE as a marker for advanced HIV.…”
Section: Discussionmentioning
confidence: 99%